Implementation of National, Regional and Local Development Strategies by Accessing Structural and Complementary Funds in the Period 2023-2027 - Cătălin LĂPĂDAT (Finanţe: Provocările viitorului, 2023)
The European Union supports, through the Structural Funds, the Cohesion Fund and financial instruments, the implementation of general objectives (convergence, regional competitiveness and employment, European territorial cooperation), for the elimination of economic and social disparities between regions, in order to achieve economic and social cohesion. The Structural Funds are not a single source of funding within the Union budget, but each fund covers its specific thematic area. They finance multiannual regional development programs drawn together by the regions, Member States and the Commission, based on the orientation proposed by the Commission for the entire European Union. The article highlights the priority objectives for the development of the Romanian economy and how they can be achieved through the financing provided by the authorities through the financing programs.